Postpostdramske reinkarnacije klasičnih tragedij - Kozak, Krištof Jacek (Amfiteater (Ljubljana), 2022)
The post-postdramatic period is characterised by a flirtation with key forms of world drama, such as ancient and Elizabethan tragedies, and their themes, which are applied to thoroughly contemporary problems. In this regard, three of the many texts can be selected: E. Jelinek’s Die Schutzbefohlenen, S. Hertmans’s Antigone in Molenbeek and V. Möderndorfer’s Romeo and Juliet Were Refugees. In addition to their relationship to antiquity, all three plays are linked by a thematic thread: migration and the unfortunate fate of refugees. It turns out that the only optimistic version of this theme came from Aeschylus, and all three contemporary plays could easily be classified as tragedies. Jelinek’s play is based on an actual event from 2012 when a group of migrants stormed the Votive Church in Vienna in protest and demanded decent asylum treatment for themselves and others like them. Jelinek exposes the whole ethical decay of Europe, which hides behind high-flying ideals of humanitarianism but does the exact opposite. In this case, it is the relationship between migrants – the real foreigners – and Europeans. Hertmans introduces a foreigner, who is already a fully-fledged citizen of Europe, only to complicate his Antigone with the classic story of the burial of a dead brother, who in this case is a terrorist. Möderndorfer takes the final step in this direction by treating economically deprived European citizens as migrants, i.e., as foreigners. None of the three plays has a way out, and the fate of the everyman ends tragically.
Keywords: Antigona; Antigone; borders; Elfriede Jelinek; meje; migracije; migration; post-postdramatic theatre; postpostdramsko gledališče; Stefan Hertmans; tragedija; tragedy; Vinko Möderndorfer